Effects of Sterilization with Different Doses of Electron Beam Irradiation on the Quality of Aronia melanocarpa Juice - LÜ Xinran, WANG Shujuan, ZHANG Dan, ZHU Tingting, SUN Xiangyu, MA Tingting (Shipin Kexue)
In this study, the effects of treatment with different doses of electron beam irradiation on physicochemical characteristics and functional components of Aronia melanocarpa juice, being rich in anthocyanins, were investigated. Meanwhile, targeted metabolomics was employed to explored the effect of irradiation treatment on the composition and content of anthocyanin metabolites in the fruit juice, and its sensory quality was evaluated as well. Irradiation treatment at 3-9 kGy increased the browning of A. melanocarpa juice, and significantly reduced the total anthocyanin content (TAC) and total polyphenol content (TPC) by 18.10%–33.72% and 2.47%–12.03%, respectively (P 0.05), whereas the contents of the other three anthocyanins were reduced significantly (P < 0.05). In term of sensory quality, irradiation treatment increased the redness and yellowness and reduced the contents of volatile sulphides and volatile terpenoids in the fruit juice. This study is expected to provide some technical references for the selection and parameter determination of irradiation processing for anthocyanin-rich foods.